Pemanfaatan Tongkol Jagung Terfermentasi untuk Ransum Sapi Bali di Kota Parepare - Semaun, Rahmawati; Tarawiru, Yasri; Wisdawati, Eka (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
The application of science and technology is expected to provide farmers with knowledge and expertise to utilize agricultural waste as ruminant feed, thereby preserving the environment and making it more useful. The training on the use of fermented corn cobs aims to train the community in dealing with agricultural waste management, improving work ethic, standard of living, and community welfare, and having high independence, and providing knowledge and skills to the community: farmers/livestock farmers, in utilizing agricultural waste through fermented corn cobs for ruminant feed. This community service activity was carried out in Watang Bacukiki Village, Bacukiki District, Parepare City. The target participants of the community service were the Mangimpuru and Locci-Locci'E Farmer Group Partners in Watang Bacukiki Village. The method used was to provide counseling and training to transfer knowledge and skills to the farmer/livestock group partners in Watang Bacukiki Village regarding agricultural waste and its impact on human health and the environment. Furthermore, trials were conducted on Bali cattle to evaluate their use as ruminant feed. The abundance of agricultural waste, namely corncobs, is often not utilized and instead burned. After receiving counseling and training on fermented corncobs, all participants understood that fermented corncobs can be used as ruminant feed. This digital marketing outreach and training activity aims to equip farmer groups with the knowledge and skills to market fermented corn cob products online. Effective digital marketing strategies are introduced, including creating promotional content, leveraging social media and e-commerce platforms, and using compelling copywriting to increase product appeal.